Health Impact and Cost-Effectiveness of Implementing Gender-Neutral Vaccination With the 9-Valent Human Papillomavirus Vaccine in Belgium - Simoens, Steven; Bento-Abreu, Andre; Merckx, Barbara; Joubert, Sophie; Vermeersch, Steve; Pavelyev, Andrew; Varga, Stefan; Morais, Edith (Frontiers in Pharmacology, 2021)
Background: Routine human papillomavirus (HPV) immunization in Belgium is currently regionally managed, with school-aged girls receiving the 9-valent HPV (9vHPV) vaccine in Flanders and Wallonia-Brussels with a national catch-up program for females only. This study will assess whether expanding these programs to gender-neutral vaccination (GNV) with the 9vHPV vaccine is a cost-effective strategy in Belgium. Methods: A validated HPV-type transmission dynamic model estimated the potential health and economic impact of regional vaccination programs, comparing GNV versus female-only vaccination (FOV) with the 9vHPV vaccine in individuals aged 11–12 years in Flanders, GNV with the 9vHPV vaccine versus FOV with the 2-valent HPV (2vHPV) vaccine in individuals aged 12–13 years in Wallonia-Brussels, and national catch-up GNV versus FOV with the 9vHPV vaccine for those aged 12–18 years. Vaccination coverage rates of 90%, 50%, and 50% in both males and females were used in the base cases for the 3 programs, respectively, and sensitivity analyses were conducted. All costs are from the third-party payer perspective, and outcome measures were reported over a 100-year time horizon. Results: GNV with the 9vHPV vaccine was projected to decrease the cumulative incidence of HPV 6/11/16/18/31/33/45/52/58-related diseases relative to FOV in both Flanders and Wallonia-Brussels. Further reductions were also projected for catch-up GNV with the 9vHPV vaccine, including reductions of 6.8% (2256 cases) for cervical cancer, 7.1% (386 cases) and 18.8% (2784 cases) for head and neck cancer in females and males, respectively, and 30.3% (82,103 cases) and 44.6% (102,936 cases) for genital warts in females and males, respectively. As a result, a GNV strategy would lead to reductions in HPV-related deaths. Both regional and national catch-up GNV strategies were projected to reduce cumulative HPV-related disease costs and were estimated to be cost-effective compared with FOV with incremental cost-effectiveness ratios of €8062, €4179, €6127 per quality-adjusted life-years in the 3 programs, respectively. Sensitivity analyses were consistent with the base cases. Conclusions: A GNV strategy with the 9vHPV vaccine can reduce the burden of HPV-related disease and is cost-effective compared with FOV for both regional vaccination programs and the national catch-up program in Belgium.